Physiotherapy Approach in Woman after Total Hysterectomy Surgery at PKU Muhammadiyah Yogyakarta Hospital: A Case Report - Mawarni, Yulia Nafizah; Widodo, Agus; Ishak, Galih Adhi (Academic Physiotherapy Conference Proceeding, 2024)
Introduction: Myoma uterine is a benign tumor in the uterus that contributes significantly to the morbidity rate worldwide. One of the surgical procedures that can be performed to remove uterine fibroids with hysterectomy. Postoperative hysterectomy is associated with a variety of complications, so an effective approach is required to prevent complications. Physiotherapy plays a role in helping recovery by avoiding and minimizing post-operative complications as well as providing rehabilitation to support the return of physical function and the patient effectively achieving a positive impact. Case Presentation: The subject is a woman, a 42-year-old office worker, in hospital after total abdominal hysterectomy with abdomen incision techniques (pfannenstiel). Has a history of constant pain during menstruation for a year and has been found to have uterine fibroids in the fundus. Management and Outcome: The intervention was given for three days after total hysterectomy surgery by providing a breathing exercise training program, circulation exercise, deep muscle activation, early transfer-ambulation exercise and bodyweight resistance exercise. Measurement and evaluation were carried out using the Numeric Rating Scale (NRS) for pain assessment. Urinary incontinence symptoms using the Questionnaire for Female Urinary Incontinence Diagnosis (QUID). Functional ability assessment using Kenny Self Care Evaluation (KSCE). Uterine Fibroid Symptom & Health-Related Quality of Life Questionnaire (UFS-QOL) to measure symptoms and evaluate health-related quality of life in women with uterine myoma. Discussion: According to the traditional view, staying on the bed after surgery should be done to reduce pain and speed wound healing, but not a few studies found that post-surgical staying has negative effects and increases the risk of complications. Various studies have found that early exercise and rapid rehabilitation interventions prevent and minimize post-abdominal surgery complications. There is pain in incisions, anxiety of reverse incision rupture, postoperative fatigue, anxiousness and other reasons patients refuse to get up from bed as well as most patients do not know how to exercise early and regulate activity after surgery, so post-operative intervention plays a role in determining whether patients can effectively a positive impact. Conclusion: This study showed that a physiotherapeutic exercise program given to patients with post-total abdominal hysterectomy was shown to reduce the level of pain, strengthen the pelvic floor muscle thus decreasing urinary incontinence, and improve the ability of functional activity.